Spectrophotometric Determinations of Pimozide and Mefloquine Hydrochloride through Ion Association Complex Formation - Mallikarjuna Rao, G.P.V.; Aruna Devi, P.; Krishna Prasad, K.M.M.; Sastry, C.S.P. (Asian Journal of Chemistry, 2010)
Three simple spectrophotometric methods (Method A, Method B and Method C) have been developed for the determination of pimozide (PZ) and mefloquine hydrochlonde (MQ) in bulk and pharmaceutical formulations. These methods are based on the formation of ion association complex involving tertiary nitrogen of PZ or secondary nitrogen of MQ and dye [wool fast blue BF (WFB BF, λmax 580 nm, method A); naphthol blue black (NBB, λmax 580 nm, method B); supracen violet 3B (SV 3B, λmax 560 nm, method C]. Beer's law limits, precision and accuracy of these methods are checked by the UV reference method. The results obtained are reproducible and are statistically validated and so found to be suitable for the assay of PZ or MQ in bulk and pharmaceutical formulations.